Prediction of Interpersonal Emotion Regulation Based on Sleep Quality and Sexual Function in Postmenopausal Women - Malek Mohammadi , Nazgol; Ansari Shahidi, Mojtaba (Psychology of Woman Journal, 2026)
Objective: This study aimed to examine the prediction of interpersonal emotion regulation based on sleep quality and sexual function in postmenopausal women.Materials and Methods: The present research was a descriptive–correlational study. The statistical population included postmenopausal women living in Karaj, Iran. A sample of 196 participants was selected using convenience sampling. The instruments used included the Pittsburgh Sleep Quality Index (PSQI), the Female Sexual Function Index (FSFI), and the Interpersonal Emotion Regulation Questionnaire (IERQ). Data were analyzed using Pearson correlation and multiple regression analysis.Findings: The results showed that both sleep quality and sexual function significantly predicted interpersonal emotion regulation. Specifically, sleep quality had a significant relationship with interpersonal emotion regulation (P < .05), and sexual function also significantly predicted interpersonal emotion regulation.Conclusion: The findings suggest that sleep quality and sexual function play an important role in predicting interpersonal emotion regulation in postmenopausal women. Accordingly, improving these two factors can contribute to enhancing psychological well-being and quality of life in postmenopausal women.